ABSENCE OF POTENTIAL BENEFIT OF PROGESTERONE PRIMING DURING OVSYNCH PROTOCOL IN POSTPARTUM ANESTROUS BUFFALO NEAR THE END OF BREEDING SEASON - Kundulkar, AD; INGAWALE, MV; DESHMUKH, SG; HAJARE, SW; INGOLE, RS (The Indian Journal of Animal Reproduction, 2016)
Lactating multiparous postpartum anestrous buffalo (>90 day in milk) were subjected to ovsynch (n=8) and ovsynch plus CIDR (n=8) and control (n=8) group treatment. The buffalo exhibiting estrus in ovsynch, ovsynch plus CIDR and control group was 100% (n=8/8), 37.5% (n=3/8) and 12.6% (n=1/8), respectively and their respective first service pregnancy rate was 50, 62.5 and 33.3% (p>0.05). In brief, the present study ruled out the potential benefit of additional progesterone priming during ovsynch protocol in postpartum anestrous buffalo treated near the end of breeding season.
Keywords: Anestrus; Buffalo; Progesterone; Postpartum; Ovsynch